Evaluation of the Skin Sensitization Potential of Carbon Nanotubes Using Alternative In Vitro and In Vivo Assays - Sung-Hyun Kim; Dong Han Lee; Jin Hee Lee; Jun-Young Yang; Hyo-Sook Shin; JeongPyo Lee; Kikyung Jung; Jayoung Jeong; Jae-Ho Oh; Jong Kwon Lee (Toxics, 2020)
Carbon nanotubes (CNTs) are one of the major types of nanomaterials that have various industrial and biomedical applications. However, there is a risk of accidental exposure to CNTs in individuals involved in their large-scale production and in individuals who use products containing CNTs. This study aimed to evaluate the skin sensitization induced by CNTs using two alternative tests. We selected single-wall carbon nanotubes and multi-walled carbon nanotubes for this study. First, the physiochemical properties of the CNTs were measured, including the morphology, size, and zeta potential, under various conditions. Thereafter, we assessed the sensitization potential of the CNTs using the ARE-Nrf2 Luciferase KeratinoSens™ assay, an in vitro alternative test method. In addition, the CNTs were evaluated for their skin sensitization potential using the LLNA: BrdU-FCM in vivo alternative test method. In this study, we report for the first time the sensitization results of CNTs using the KeratinoSens™ and LLNA: BrdU-FCM test methods in this study. This study found that both CNTs do not induce skin sensitization. These results suggest that the KeratinoSens™ and LLNA: BrdU-FCM assay may be useful as alternative assays for evaluating the potential of some nanomaterials that can induce skin sensitization.